Utilizing enantiomerically pure organic spacers for anion-centred clusters in a hybrid inorganic-organic lead-halide crystal - Heindl, Markus W.; Ballmann, Joachim; Deschler, Felix (Chemical communications, 2025)
In this work, we present structural data of the novel, chiral material (S-2AH)4[Pb2Br7]Br obtained from single crystal X-ray diffraction (SCXRD). This quasi-2D material displays anion-centred clusters within its organic layer, without the need for bi-functional spacers. Instead, the structure is based on the steric properties of the used enantiomerically pure precursors.